Early Detection of Oncological Diseases of the Digestive System (Guidelines of the Russian Gastroenterological Association and the Russian Association of Oncologists for Primary Care Physicians) - V. T. Ivashkin; I. V. Mayev; A. D. Kaprin; M. Yu. Agapov; D. N. Andreev; A. S. Vodoleev; M. Yu. Zharkova; M. P. Korolev; Yu. A. Kucheryavyi; T. L. Lapina; M. V. Mayevskaya; A. V. Okhlobystin; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The present guidelines intended for primary care physicians are aimed at facilitating early diagnosis of malignant tumours of the digestive system, which can significantly improve the immediate and long-term results of their treatment.General provisions. The guidelines comprise sections devoted to esophageal adenocarcinoma, esophageal squamous cell carcinoma, gastric cancer, colorectal cancer, hepatocellular carcinoma and extrahepatic bile duct and gall bladder cancer, as well as pancreatic cancer. Each section contains information on risk factors and precancerous diseases, which allows a physician to identify whether a particular patient falls into the risk group of digestive system neoplasms. It is shown how digestive system cancers can be suspected on the basis of patients’ complaints and past medical history, as well as data obtained both from a direct examination and laboratory instrumental studies. Each section offers practical algorithms in cases of suspected esophageal adenocarcinoma, esophageal squamous cell carcinoma, gastric cancer, colorectal cancer, hepatocellular carcinoma and extrahepatic bile duct and gallbladder cancer, as well as pancreatic cancer.Conclusion. The knowledge of clinical manifestations and risk factors in the development of digestive system neoplasms allows a physician to suspect cancer and devise a timely and adequate diagnostic strategy, including laboratory and instrumental studies at specialised clinical centres.